2004
DOI: 10.1177/0310057x0403200110
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Evaluation of the Single-use SoftSeal and the Re-useable LMA Classic Laryngeal Mask

Abstract: A number of laryngeal masks are available, including both re-usable and single-use masks. Single-use laryngeal masks may decrease the risk of transmitting prion infections. We performed a single-blind randomized trial in 200 spontaneously breathing female patients under general anaesthesia with nitrous oxide, to compare a new single-use laryngeal mask, the SoftSeal™ (Portex Ltd, U.K.), with a re-usable laryngeal mask, the LMA Classic™ (Laryngeal Mask Company Ltd., Cyprus). The primary outcome was successful in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
25
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 27 publications
8
25
3
Order By: Relevance
“…However, this potential advantage had no clinical implication because it did not result in improved ventilation in this group and airway pressure was easily maintained below sealing pressure in all patients. Our results are in agreement with those of Paech et al [13], Tan et al [21], Cook et al [18], and Francksen et al [22], who reported a better airway seal with the Soft Seal than the LMA Unique. In contrast, Brimacombe et al [16] found no differences in leak pressure between the Soft Seal and the LMA Unique in paralyzed patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, this potential advantage had no clinical implication because it did not result in improved ventilation in this group and airway pressure was easily maintained below sealing pressure in all patients. Our results are in agreement with those of Paech et al [13], Tan et al [21], Cook et al [18], and Francksen et al [22], who reported a better airway seal with the Soft Seal than the LMA Unique. In contrast, Brimacombe et al [16] found no differences in leak pressure between the Soft Seal and the LMA Unique in paralyzed patients.…”
Section: Discussionsupporting
confidence: 93%
“…In most cases, the presence of blood was minimal and did not correlate with pain during recovery. Paech et al [13], Cook et al [18], and Tan et al [21] found a similar frequency of mucosal trauma with the Soft Seal. However, van Zundert et al [12] reported macroscopic blood in only 4% of laryngeal mask uses, all from the LMA Classic group.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The disposable laryngeal mask avoids this cross infection risk, particularly in relation to prion transmission. 25 Although there are numerous manikin studies comparing laryngeal mask insertion or endotracheal intubation, there is a need for more quantitative clinical studies comparing the two devices. We therefore designed a study to compare the time taken to secure the airway using laryngeal mask insertion and endotracheal intubation in patients undergoing elective surgical procedures to assess whether any difference exists between the two devices.…”
mentioning
confidence: 99%